Consumer behavior among dog owners : How trends spread from the US to small businesses in Finland - Melkko, Adele (fi=Turun yliopisto|en=University of Turku|, 2018)
This study discusses the consumer behavior and trends in the dog commodity market in Finland and in the US using qualitative methods. The aim of this study is to find out what kind is the consumer behavior in this market with the sub-objective of discovering the prevalent dog commodity trends and thus creating a coherent picture of the market. This is achieved by Internet content analysis, and small business entrepreneur interviews and dog-owning consumer interviews. The understanding of the market from both, the supply and demand sides, makes it easier for operators to see the full potential of the market and this way benefit from it. The theoretical frame consists of knowledge on consumer behavior, emotions in consuming, trends and their diffusion ways, the human-dog relationship and small businesses. These themes support the understanding of the dog commodity market, how it operates and what the driving forces behind the growth of the market are. A synthesis and a process picture of how the trends spread from the US to Finland are created, which illustrate how WOM and eWOM seem to have a substantial role in the spreading of trends in the dog commodity market. Another of the main discoveries here was the strong role of emotions in this market. The conclusions of this study are that the US is a strong influencer and seems to be the main influencer on the Finnish dog commodity market. The Internet is the most used trend following method among entrepreneurs and consumer informants. Especially social media and discussion forums have a lot of value as they provide needed peer support. In addition, the type of relationship between a dog and its owner is a major influencer on the consumer behavior in this market and different consumer types follow and spread trends in different ways. Furthermore, there is still a lot of potential in this market, especially in the dog service sector. Health and a dog as a companion are themes that will most likely grow their roles in the market.